PENGARUH PEMANFAATAN LINGKUNGAN ALAM SEKITAR SEBAGAI MEDIA DAN SUMBER PEMBELAJARAN IPAS DI KELAS III SDN 40/1 BAJUBANG LAUT - Khoirunnisa; Andin Ersa Putri; Zahro Lailaturrohmah; Siti Rahayu; Liansyah Fitra (STKIP Subang, 2026)
This study aims to analyze the use of learning resources from the surrounding natural environment in teaching living things in third-grade students at SDN 40/1 Bajubang Laut. This study employed qualitative methods with a descriptive approach, conducted through observation, interviews, and document analysis. The findings indicate that utilizing the surrounding environment as a learning tool can deepen students' understanding of scientific concepts, particularly the topic of living things. Furthermore, the use of nature-oriented learning resources also encourages active student participation, curiosity, and direct involvement in the learning process. This study found that despite challenges in developing teaching materials and the need for teacher innovation, the natural environment can serve as an effective learning resource to support science education in elementary schools if supported by careful planning.